Thermal symmetry of healthy feet: a precursor to a thermal study of diabetic feet prior to skin breakdown. (12th December 2016) - Macdonald, Audrey; Petrova, Nina; Ainarkar, Suhail; Allen, John; Plassmann, Peter; Whittam, Aaron; Bevans, John; Ring, Francis; Kluwe, Ben; Simpson, Rob; Rogers, Leon; Machin, Graham; et al.
Abstract: Early identification of areas of inflammation may aid prevention of diabetic foot ulcers. A new bespoke thermal camera system has been developed to thermally image feet at risk. Hotspots (areas at least 2.2 °C hotter than the contralateral site) may indicate areas of inflammation prior to any apparent visual signs. This article describes the thermal pattern and symmetry of 103 healthy pairs of feet. 68% of participants were thermally symmetric at the 33 foot sites measured. 32% of participants had at least one hotspot, but hotspots overall only accounted for 5% of the measurements made. Refinements to the definition of hotspots are proposed when considering feet at risk of ulceration.